Devil's gulch - Johnstone, William W.; Johnstone, J. A. (Devil's Gulch western, 2023)
The bestselling Johnstones deliver their second book featuring Ben Savage, a former Texas Ranger-turned bar owner in the rough and tough town of Buzzard's Bluff. The Texas Rose Saloon has a reputation for attracting the wildest characters the Wild West has to offer. But there's a new owner in town, and when a former lawman like Ben Savage is at the bar, there are two kinds of shots on order: the kind that come from a bottle of whiskey...and the kind that come from the barrel of his gun. -Amazon.